Theoretical research and optimization analysis for the injection process of the single screw refrigeration compressor. (April 2018) - Wang, Zengli; Shen, Yingfeng; Wang, Zhenbo; Wang, Jun; Jiang, Wenchun; Li, Qiang
Highlights: Theoretical models of SSRC with injection have been established. The actual capacity and injection quality of the SSRC can be obtained. Influences of the structural parameters on the SSRC with injection are analyzed. Smaller the initial position and larger diameter of the injection hole need to be chosen. Abstract: In single screw refrigeration compressor (SSRC), the liquid refrigerant injected into the working chamber is used to reduce the exhaust gas temperature and improve the compressor performance. In this paper, a new calculation model of the injection process considering internal compression, leakage and heat transfer is presented based on the meshing principle of the meshing pair and the working mechanism of the SSRC with injection. By this model, the actual capacity and injection quality can be obtained using the calculated effective injection area. The influence of the structural parameters such as the initial position and the injection-hole diameter to the characteristics of the injection process and the thermodynamic properties of the SSRC are analyzed. Through the comparison of the injection process with different structural parameters, optimization analysis of the structural parameters can be obtained. All of this work can provide the basis for the later optimization design of the injection process.